The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.1080/10673220490425924
|View full text |Cite
|
Sign up to set email alerts
|

Antisuicide Properties of Psychotropic Drugs: A Critical Review

Abstract: The authors consider the extent to which psychotropic medications demonstrate benefits in the prevention of suicidal behavior in psychiatric patients. Results of a MedLine search are critically reviewed for lithium, divalproex and other anticonvulsants, conventional and atypical antipsychotics, and antidepressants. The existing literature is almost entirely limited to noncontrolled, often retrospective studies that do not control for potential biases in treatment selection, the use of multiple medications, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 167 publications
0
33
0
1
Order By: Relevance
“…Risk of suicide appears to be greater among psychotic disorder patients who are younger, male, never married, with evidence of current or previous depression or substance abuse, as well as previous suicide attempts, and who have had relatively good premorbid functioning [8,10,11]. Evidence that older, typical neuroleptic drugs, alone or with antidepressants added, alter suicidal risks in schizophrenia patients, either favorably or unfavorably, is limited and inconsistent [8,12,13,14]. Risk of mortality due to natural causes, including sudden death presumably related to cardiac dysfunction, may be increased with older neuroleptics as well as with modern atypical or second-generation antipsychotics (SGAs) [15,16].…”
Section: Resultsmentioning
confidence: 99%
“…Risk of suicide appears to be greater among psychotic disorder patients who are younger, male, never married, with evidence of current or previous depression or substance abuse, as well as previous suicide attempts, and who have had relatively good premorbid functioning [8,10,11]. Evidence that older, typical neuroleptic drugs, alone or with antidepressants added, alter suicidal risks in schizophrenia patients, either favorably or unfavorably, is limited and inconsistent [8,12,13,14]. Risk of mortality due to natural causes, including sudden death presumably related to cardiac dysfunction, may be increased with older neuroleptics as well as with modern atypical or second-generation antipsychotics (SGAs) [15,16].…”
Section: Resultsmentioning
confidence: 99%
“…32 The antisuicidal effect estimated here is larger than the effect on mood episodes, 27 28 raising the possibility of a specific effect. 33 Possible mechanisms include an effect on aggression or impulsivity, both of which are associated with an increased risk of suicide. 32 34 Lithium may decrease aggression and possibly impulsivity, 35 which might mediate its antisuicidal effect.…”
Section: Implication For Researchmentioning
confidence: 99%
“…One review investigating the effects of first-generation antipsychotics on suicide rates demonstrated a modest advantage in patients with schizophrenia [102]. However, in considering this in the elderly, there is a concern of a higher rate of extrapyramidal, anticholinergic and sedating side effects which could arise with these agents in this population [103]. In studies examining individuals of all ages, extrapyramidal side effects have been associated with dysphoria, worsening subjective distress, agitation and suicidal behavior [104,105].…”
Section: Developing Cognitive Behavioral Approaches To Treat the Oldementioning
confidence: 99%
“…Ernst and Goldberg point out many of the methodological limitations of the investigations utilizing first-generation antipsychotic medications [103]. They state that many results appear to be confounded by retrospective study design, treatment assignments lacking randomization, recall bias, varying medication regimens and lack of control for comorbid psychiatric diagnoses.…”
Section: Developing Cognitive Behavioral Approaches To Treat the Oldementioning
confidence: 99%
See 1 more Smart Citation